Integritas Kepemimpinan Kepala Sekolah dalam Meningkatkan Kompetensi Profesional Guru PAI - Hasannah, Annis Watun; Rudiyanto, Rudiyanto (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The leadership behavior of a school principal who has an attitude of integrity is very much needed in an educational institution. So the aim of this research is to identify the integrity leadership attitude of school principals in improving the professional competence of Islamic Religious Education (PAI) teachers and identify obstacles to the leadership integrity attitude of school principals in improving the competency of Islamic Religious Education (PAI) teachers. The research method applied is a qualitative approach with descriptive research type. Data collection was carried out through interviews, observation and documentation. The research results show that the integrity leadership attitude of the principal at SD Plus Nurul Hikmah involves elements such as honesty, happiness in service, and commitment. Even though there are relatively minimal internal obstacles due to routine coaching and evaluation activities, there are external obstacles, especially from student parents who lack control over children's development at home.